Online Counseling for Mental Health: Evaluating its Impact on Coping Strategies Among University Students during the Pandemic - Adi Laksono (P3M STAI Kuningan, 2025)
Background: The COVID-19 pandemic forced university mental health services to transition from traditional face-to-face counseling to online platforms as students experienced heightened anxiety, depression, and academic stress.Objective: This study evaluates the impact of online counseling interventions on university students' coping strategies during the pandemic, examining effectiveness, accessibility, and implementation challenges.Method: A narrative review synthesized 45 empirical studies published between 2019 and 2025, including randomized controlled trials, quasi-experimental designs, and qualitative investigations of various modalities (teletherapy, video counseling, chatbots, mobile applications).Findings and Implications: Findings demonstrate that online counseling achieved outcomes comparable to pre-pandemic face-to-face services, with moderate to large effect sizes () for symptom reduction and therapeutic alliance. Video counseling proved most effective for complex presentations, while AI chatbots benefited students with mild symptoms. Online interventions improved accessibility and enabled students to develop adaptive coping strategies with flexible real-world application.Conclusion: The study recommends integrating online counseling into hybrid models through institutional policy frameworks, evidence-based modality selection guidelines, and strategic infrastructure development to ensure sustainable, equitable mental health access in higher education.